2017
DOI: 10.1098/rsos.161081
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific association patterns in bonobos and chimpanzees reflect species differences in cooperation

Abstract: In several group-living species, individuals' social preferences are thought to be influenced by cooperation. For some societies with fission–fusion dynamics, sex-specific association patterns reflect sex differences in cooperation in within- and between-group contexts. In our study, we investigated this hypothesis further by comparing sex-specific association patterns in two closely related species, chimpanzees and bonobos, which differ in the level of between-group competition and in the degree to which sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 126 publications
(210 reference statements)
0
51
1
Order By: Relevance
“…We tentatively propose that these results can be best explained by the leadership hypothesis [23,24,26]. The co-dominance between the sexes and high degree of female gregariousness in bonobos [25] may contribute to the lack of a defined leader and explain why bonobos were, on average, the most neophobic of the three great apes. A recent study on leadership in wild bonobos found that multiple older females were central to group movement decisions [36].…”
Section: Species Differences In Looking Impulse and Neophobic Responsesmentioning
confidence: 90%
See 1 more Smart Citation
“…We tentatively propose that these results can be best explained by the leadership hypothesis [23,24,26]. The co-dominance between the sexes and high degree of female gregariousness in bonobos [25] may contribute to the lack of a defined leader and explain why bonobos were, on average, the most neophobic of the three great apes. A recent study on leadership in wild bonobos found that multiple older females were central to group movement decisions [36].…”
Section: Species Differences In Looking Impulse and Neophobic Responsesmentioning
confidence: 90%
“…Additionally, the leadership hypothesis, initially proposed for schools of fish [23], suggests that in species lacking a clear leader (i.e., egalitarian), individual personalities strongly predict group decisions about where to feed and rest [16,24]. The allocation of risk is predicted to be spread more evenly within the group in more egalitarian species, such as bonobos [25], rather than resting solely on one or a few dominant individuals, as in gorillas and chimpanzees [26]. Captive experiments have shown that bonobos are more neophobic and risk-averse than chimpanzees or orangutans and exhibit novelty responses more similar to those of human children [7,8].…”
Section: Species-dependent Variation To Noveltymentioning
confidence: 99%
“…They live in male‐philopatric multi‐male/multi‐female groups with stable memberships, which may split into temporary “parties” (fission–fusion grouping patterns, Kano, ; Sakamaki et al, ). Unlike other species, in which individuals of the philopatric sex usually have stronger association, affiliative, and cooperative relationships than the dispersing sex, association and affiliative behaviors in bonobos are more frequently observed among females, except for mother–offspring pairs (Furuichi, ; Moscovice et al, ; Surbeck et al, ; White, ). Male bonobos rarely form coalitions, but the females often form coalitions to attack the males, which may lead to within‐group high social status for the females (Parish, ; Surbeck & Hohmann, ; Tokuyama & Furuichi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the number of available data is still scarce, duration of maternal carriage of their dead offspring may be longer in chimpanzees than in bonobos. This may be because female bonobos are more social than female chimpanzees (Kano 1992;Furuichi 2009;Surbeck et al 2017). Mother bonobos may choose to leave their dead offspring in order to perform intense social interactions with other alive conspecifics.…”
Section: Discussionmentioning
confidence: 99%